Fossil-calibrated phylogenies of Southern cave wētā show dispersal and extinction confound biogeographic signal - Dowle EJ; Trewick SA; Morgan-Richards M (The Royal Society, 2024)
The biota of continents and islands are commonly considered to have a source-sink relationship, but small islands can harbour distinctive taxa. The distribution of four monotypic genera of Orthoptera on young subantarctic islands indicates a role for long-distance dispersal and extinction. Phylogenetic relationships were inferred from whole mtDNA genomes and nuclear sequences (45S cassette; four histones). We used a fossil and one palaeogeographic event to calibrate molecular clock analysis. We confirm that neither the Australian nor Aotearoa-New Zealand Rhaphidophoridae faunas are monophyletic. The radiation of Macropathinae may have begun in the late Jurassic, but trans-oceanic dispersal is required to explain the current distribution of some lineages within this subfamily. Dating the most recent common ancestor of seven island endemic species with their nearest mainland relative suggests that each existed long before their island home was available. Time estimates from our fossil-calibrated molecular clock analysis suggest several lineages have not been detected on mainland New Zealand, Australia, or elsewhere most probably due to their extinction, providing evidence that patterns of extinction, which are not consistently linked to range size or lineage age, confound biogeographic signal.
Keywords: cave crickets; dispersal; extinction; mitogenome; molecular clock; subantarctic